An evaluation of the programs implemented by the NGOs and government to promote children`s rights: a focus on illegal child migrants in ward 5 Mwenezi district in Zimbabwe. - Ncube, Samukeliso (Midlands State University, 2017)
The focus of the study was to evaluate implemented program by the government and NGOS In trying to promote children`s rights on children on the move: A focus on illegal child migrants in ward 5 Mwenezi District Zimbabwe. The research was qualitative in nature and purposive sampling was used as easiest way of sampling the research participants’ during this research .it focused on the group of people who once migrated illegal and they have got detailed information on the living experience. Government departments and NGOs which has something to do the children`s rights also participated in this research with relevant information. These key informants include those from social service, plan international, . The area of study was Mwenezi district ward 5 in Zimbabwe. The people in Mwenezi depend much on subsistence farming and cross border trade; it has been found that the sector of farming is being affected due to poor rainfall in the region. Mwenezi district is a semi –extensive rainfall region which receive poor rainfall hence follow by drought leading to poverty. This means that cross border trade is now dominant survival strategy in Mwenezi district ward 5.Poverty will not affect the elders but children are also being affected especial the most vulnerable children. The officer from social service postulate that orphans are the major group in Mwenezi which is most vulnerable to illegal child migration as they see their elders indulging in cross border trade. By so doing they have seen S.A as their messiah to dileunma at home not noticing that by illegal migration they will be undermined their rights.